2011
DOI: 10.1017/s1368980010003058
|View full text |Cite
|
Sign up to set email alerts
|

Assessing factorial and convergent validity and reliability of a food behaviour checklist for Spanish-speaking participants in US Department of Agriculture nutrition education programmes

Abstract: Objective To assess convergent validity, factorial validity, test–retest reliability and internal consistency of a diet quality food behaviour checklist (FBC) for low-literate, low-income Spanish speakers. Design Participants (n 90) completed three dietary recalls, the Spanish-language version of the US Department of Agriculture (USDA) Household Food Security Survey Module (HFSSM) and the Spanish-language FBC. Factor structure was examined using principal component analysis. Spearman correlation coefficients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…This item did not perform well when a Spanish-language version of the questionnaire was tested in low-income Spanish speakers and was selected for deletion. 17 If it is found not to correlate with nutrient intake in future studies, this item may be modified and tested further, or may be considered for deletion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This item did not perform well when a Spanish-language version of the questionnaire was tested in low-income Spanish speakers and was selected for deletion. 17 If it is found not to correlate with nutrient intake in future studies, this item may be modified and tested further, or may be considered for deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in a previous study evaluating a Spanish-language FBC, in which the correlation coefficient for the 2 milk and dairy items was also low. 17 This low correlation may have indicated that the 2 items reflected different behaviors within the dairy domain construct. None of the subscales had Cronbach α ≥.90, which suggests redundancies of items.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the study population, design, and method have been published previously and are presented briefly below. 31 The institutional review board from the University of California, Davis approved the study protocol and all participants provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%